Development of Physics Learning Media Integrated with Artificial Intelligence and Islamic Values on Free Fall Motion Material - Mulia Rahmi; Mariati Mariati; Zakiah Zakiah; Muslimatul Walidah; Yusrizal Hasja (Darul Yasin Al Sys, 2026)
The need for innovative physics learning media that integrate Artificial Intelligence (AI) and Islamic values has become increasingly important in supporting meaningful science learning, particularly in abstract topics such as free fall motion. This study aimed to develop AI-based physics learning media integrated with Islamic values for students at SMP Tastafi Abu Lamkawe, Pidie Regency, Aceh. The study employed a Research and Development (R&D) method using the ADDIE model. Data were collected through expert validation and student response questionnaires. The findings showed that the developed media obtained a material expert validation score of 72.2%, categorized as feasible; a media expert validation score of 84%, categorized as feasible; a tafsir expert validation score of 73.3%, categorized as feasible; and a student response score of 79.54%, indicating positive and effective use. The media integrated Islamic values by encouraging tafakkur in understanding free fall phenomena as part of sunnatullah. These findings indicate that the developed media is valid, feasible, and effective for supporting physics learning. The study contributes to the development of integrative science education by demonstrating the potential of AI-based learning media to connect scientific concepts with Islamic values, while providing practical implications for teachers and educational institutions in designing innovative, spiritually oriented physics learning resources.